Drug survival of IL-12/23, IL-17 and IL-23 inhibitors for moderate-to-severe plaque psoriasis: a retrospective multicenter real-world experience on 5932 treatment courses – IL PSO (Italian landscape psoriasis) - Gargiulo, Luigi; Ibba, Luciano; Malagoli, Piergiorgio; Balato, Anna; Bardazzi, Federico; Burlando, Martina; Carrera, Carlo G.; Damiani, Giovanni; Dapavo, Paolo; Dini, Valentina; Gaiani, Francesca M.; Girolomoni, Giampiero; et al. (Frontiers in Immunology, 2024)
The development of several effective biological drugs for moderate-to-severe plaque psoriasis has dramatically changed the lives of patients. Despite the wide use of interleukin (IL) inhibitors, limited data are available to date regarding long-term treatment persistence.Method: This multicenter retrospective real-world study evaluated 5932 treatment courses across 5300 patients, all treated with interleukin inhibitors. Drug survival was expressed by using the Kaplan-Meier estimator for each biological drug at 6, 12, 24, 36 and 48 months. We also stratified by discontinuation associated with primary or secondary ineffectiveness.Results: In our study, the most prescribed drugs were secukinumab (1412), ixekizumab (1183), and risankizumab (977). After four years of follow-up, risankizumab emerged as the treatment with the highest drug survival overall, as 91.6% of patients were still on treatment. The overall probability of drug survival at four years was comparable for tildrakizumab (83.5%), ixekizumab (82.6%), guselkumab (82.4%) and brodalumab (81.8%). When evaluating only patients who discontinued the treatment because of ineffectiveness, once again risankizumab was the molecule with the highest drug survival at 4 years (93.4%), this time followed by ixekizumab (87%). Our study, in which all IL inhibitors were adequately represented, confirmed a slightly better treatment persistence for IL-23 inhibitors, consistent with other real-world studies.Our experience showed that IL-23 inhibitors, and risankizumab in particular, had a higher probability of drug survival overall during a 4-year follow-up. Risankizumab and ixekizumab were less likely to be discontinued because of ineffectiveness after four years.